Engaging Students in Sustainable Science Education - Grabau, Larry J. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue (Engaging Students in Sustainable Science Education) compiled effective approaches to student engagement in science-related classes. Some articles were written by researchers in science education; however, the majority were prepared by college and university instructors based on their own instructional approaches, and were designed to help other practitioners improve student engagement in scientific contexts. Both types of contributors added value to this conversation. This Special Issue serves to unite science and education, identifying approaches that create stimulating scientific learning environments.